Embracing plant plasticity or robustness as a means of ensuring food security - Saleh Alseekh; Annabella Klemmer; Jianbing Yan; Tingting Guo; Alisdair R. Fernie (Nature Communications)
Abstract The dual challenges of global population explosion and environmental deterioration represent major hurdles for 21st Century agriculture culminating in an unprecedented demand for food security. In this Review, we revisit historical concepts of plasticity and canalization before integrating them with contemporary studies of genotype-environment interactions (G×E) that are currently being carried out at the genome-wide level. In doing so we address both fundamental questions regarding G×E and potential strategies to best secure yields in both current and future climate scenarios.